Response of Maize (Zea mays L.) genotypes to temperature and light intensity under green-house and field conditions - Ahmed, Shilan Mahmood; Muhamad, Aram A. (Journal of Kerbala for Agricultural Sciences, 2018)
The present investigation was conducted at the Qlyasn Agricultural Research Station - Faculty of Agricultural Sciences, during the summer season of 2011. The study included two different experiments , field and green house experiments. Randomized complete block design (RCBD) design was used in the field experiment with four replication . Four maize Zea mays L. genotypes , obtained from different sources were cultivated under the natural condition in the field experiment in experimental units with ( 4 x 2.5 m) area , the length of rows was 4 meters and distance between each two rows was 0.70 m , and 0.25m between every two plants. While light intensity was measured by PHYWE –Type- LUX Meter, shading was used for diminishing over heat, and light-bulbs were used for balancing light interception inside the green house. There were significant differences among maize genotype responses under the effect of temperature and light intensity of field conditions in studied vegetative growth criteria except plant height and chlorophyll content which were measured in second date post- silking . There were significant differences in accumulated numbers of CHUs among genotypes , in which G1 needed minimum numbers of CHUs (2121.600) , while G3 needed maximum numbers of CHUs (2346.625) and there were differences in the distribution pattern of the accumulated heat units on the growth stages of the genotypes. There were significant differences among four maize genotypes in the rate of leaf appearance across the growth season, and in the number of CHUs required for phyllochron in different stages of growth , and the superiority was to G3 compared to other genotypes. The significant exceeding of G3 also was in LAI due to larger numbers of leaves.